2010
DOI: 10.1002/jbio.200900099
|View full text |Cite
|
Sign up to set email alerts
|

Application of aluminum phthalocyanine nanoparticles for fluorescent diagnostics in dentistry and skin autotransplantology

Abstract: This paper deals with the possibility of application of aluminum phthalocyanine (AlPc) nanoparticles in clinical practice. AlPc fluoresces in the molecular form but in the form of nanoparticles it does not. Separation of molecules from an AlPc nanoparticle and therefore the appearance of fluorescence occurs under the effect of a number of biochemo‐physical factors. Owing to this feature the application of AlPc nanoparticles followed by the measurement of fluorescence spectra is proposed as a diagnostics method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…38 Similarly, aluminum-phthalocyanine mediated PDT has also been associated with growth promoting effect on osteoblast cells. 39 The role of PDT is of interest in cures of autoimmune diseases especially RA. 40 In previous studies we reported a new therapeutic effect of photoactivated TSPP-TiO 2 nanocomposites on RA.…”
Section: Discussionmentioning
confidence: 99%
“…38 Similarly, aluminum-phthalocyanine mediated PDT has also been associated with growth promoting effect on osteoblast cells. 39 The role of PDT is of interest in cures of autoimmune diseases especially RA. 40 In previous studies we reported a new therapeutic effect of photoactivated TSPP-TiO 2 nanocomposites on RA.…”
Section: Discussionmentioning
confidence: 99%
“…O diagnóstico fotodinâmico também pode ser utilizado com sucesso para a classificação de risco da rejeição de enxertos de pele, por meio do monitoramento dos espectros de fluorescência de monômeros como o cloro alumino ftalocianina (ALPC) (VASILCHENKO et al, 2010). O ALPC é um fotossensibilizador que fluoresce na forma molecular, mas sob a forma de nanopartículas isso não acontece, dessa forma, utiliza-se nanopartículas hidrofóbicas como carreadoras do ALPC para o interior de macrófagos e neutrófilos.…”
Section: Outras Aplicaçõesunclassified
“…We have previously discovered the effect of changes in the absorption and fluorescence spectra, the dynamics of interaction with laser radiation (photobleaching), and the fluorescence lifetime of self-aggregated AlPcCl nanoparticles upon changes in colloid pH, capture by immune cells (monocytes [ 35 ] and macrophages [ 36 ]), interaction with bacteria [ 37 , 38 ], and ingress of these particles into inflamed biological tissue [ 35 , 39 ]. We suggest that registration and characterization of changes in the spectral properties of AlPc NPs accumulated by malignant or tumor-associated cells can make it possible to assess the direction of the tumor process.…”
Section: Introductionmentioning
confidence: 99%